2016
DOI: 10.1016/j.jclepro.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The spatial-temporal characteristics and health impacts of ambient fine particulate matter in China

Abstract: a b s t r a c tAirborne particulate matter presents a serious health threat to human beings, but in China there have until now been few epidemiological studies, especially regarding the impact of ambient fine particulate matter (PM 2.5 ). This study explored first the temporal and spatial characteristics of ambient airborne PM 2.5 in China, 2013. Mortality, respiratory diseases, cardiovascular diseases, and chronic bronchitis were then evaluated as four health endpoints attributed to PM 2.5 . The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(52 citation statements)
references
References 49 publications
1
49
1
1
Order By: Relevance
“…The relative risk (RR) for the given health outcome can be calculated using the following equation (23,24):…”
Section: Health Risk Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative risk (RR) for the given health outcome can be calculated using the following equation (23,24):…”
Section: Health Risk Assessmentmentioning
confidence: 99%
“…Respiratory disease is a general term for such illnesses as pneumonia, asthma, acute tonsillitis, influenza, and chronic obstructive pulmonary diseases (COPD) including emphysema and chronic bronchitis. However, chronic bronchitis was calculated separately as individual health outcome similarly to many other studies (23,24).…”
Section: Health Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…lower respiratory infections, trachea bronchus, lung cancers and cerebrovascular disease) (Lelieveld et al 2015;Liu et al 2016). It has been estimated that PM2.5 pollution in urban areas of China led to 763,595 premature deaths in 2013 (Song et al 2016). Beijing was worst affected with estimates of 5.2, 9.0, 2.3, and 1.6 thousand premature mortalities from ischemic heart disease (IHD), cerebrovascular disease, chronic obstructive pulmonary disease (COPD) and lung cancer (LC), respectively (Liu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that fine particulate matter less than 2.5 µm in diameter (PM 2.5 ) have serious adverse effects on human health, affecting the lungs and alveolar regions, while ultrafine particles (˂ 0.1 µm) may be transported into the systemic circulation (Song et al, 2016).…”
Section: Introductionmentioning
confidence: 99%